Production of Extracellular Enzymes by Pathogenic Vibrio spp. in Fish - K., Dhevendaran; M.I., Georgekutti (Fishery Technology, 2025)
Production of extracellular enzymes and haemolysin in a few species of Vibrio was examined. Majority of Vibrio spp. produced lipase, protease and arylsulfatase. More than 90% of the strains released haemolysin on fish blood agar and a few on calf blood and sheep blood agar. Representative strains isolated from fish showed lethality against white mice. Infected parts of fish harboured arylsulfatase producing bacteria. The pH activity curve of arylsulfatase showed a primary peak at pH 5.2 and secondary peak at pH 6.2.